2014
DOI: 10.1007/s00410-014-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of amphiboles: implications for oxygen fugacity and water activity in lithospheric mantle beneath Victoria Land, Antarctica

Abstract: Amphibole is the hydrous metasomatic phase in spinel-bearing mantle xenoliths from Baker Rocks, Northern Victoria Land, Antarctica. It occurs in veins or in disseminated form in spinel lherzolites. Both types derive from reaction between metasomatic melts and the pristine paragenesis of the continental lithospheric mantle beneath Northern Victoria Land. To determine the effective role of water circulation during the metasomatic process and amphibole formation, six amphibole samples were fully characterized. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 79 publications
2
18
1
Order By: Relevance
“…The same observations have been reported in previous studies (Yang et al, 2008;Schmädicke et al, 2013;Bonadiman et al, 2014;Denis et al, 2015). Bonadiman et al However, it is noteworthy that these two Amp-bearing samples have higher / ratios than the / ratio range restricted by mantle xenoliths from worldwide localities (Table 5; Fig.…”
Section: Water Content Variation Controlled By Different Processessupporting
confidence: 89%
“…The same observations have been reported in previous studies (Yang et al, 2008;Schmädicke et al, 2013;Bonadiman et al, 2014;Denis et al, 2015). Bonadiman et al However, it is noteworthy that these two Amp-bearing samples have higher / ratios than the / ratio range restricted by mantle xenoliths from worldwide localities (Table 5; Fig.…”
Section: Water Content Variation Controlled By Different Processessupporting
confidence: 89%
“…error ¼ 1r). Bonadiman et al (2014) also reported the oxygen fugacity of amphibole-bearing mantle xenoliths, based on oxy-amphibole equilibrium; these give Dlog fO 2 values between -1Á32 and -2Á52. Figure 12 shows fO 2 data from xenoliths in continental rifts and various tectonic settings from around the world.…”
Section: Oxygen Fugacitymentioning
confidence: 99%
“…They obtained Dlog fO 2 values between -0Á2 and -1Á5 for spinel peridotite specimens. Bonadiman et al (2014) reported Dlog fO 2 values from anhydrous olivineorthopyroxene-spinel equilibria of between -0Á30 and -1Á98, which suggests a relatively consistent oxygen fugacity for the anhydrous shallow, rifted, spinel peridotite mantle beneath Victoria Land with a median value of -1Á0 6 0Á1 Dlog fO 2 (n ¼ 20; range -1Á98 to -0Á2; McDonough, 1990); DMM, depleted MORB-source mantle (Workman & Hart, 2005). The HIMU pattern is for Mangaia, Austral Islands [sample M-11 of Woodhead (1996)].…”
Section: Oxygen Fugacitymentioning
confidence: 99%
See 2 more Smart Citations